2019
DOI: 10.1111/fwb.13384
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen important questions in the spatial ecology of diatoms

Abstract: Recently, studies about the spatial distribution of microbial species and communities have increased substantially. Freshwater diatoms are used as one of the most popular model taxa in such macroecological studies, but the most exciting patterns in the spatial ecology of diatoms have not been reviewed. Here, we identify 15 important questions about freshwater diatom ecology, review the major findings, and suggest novel research avenues. We found that diatoms do not support classical latitudinal diversity gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 106 publications
(188 reference statements)
2
35
0
Order By: Relevance
“…For most other groups of aquatic organisms, however, the prevailing view was that they mostly have cosmopolitan distributions resulting from their generally large population sizes and high dispersal capacities (Fontaneto 2019). Consequently, local occurrence of most aquatic taxa is thought to be largely determined by environmental selection (Soininen and Teittinen 2019), and the application of broad morphological species concepts reinforced this idea (Vyverman et al 2010). Recent taxonomic studies, however, based on multiple lines of evidence (including genetic data), have revealed the existence of widespread (semi‐)cryptic diversity, restricted geographical distributions and regional endemism in many groups (April et al 2011, Kotov and Taylor 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For most other groups of aquatic organisms, however, the prevailing view was that they mostly have cosmopolitan distributions resulting from their generally large population sizes and high dispersal capacities (Fontaneto 2019). Consequently, local occurrence of most aquatic taxa is thought to be largely determined by environmental selection (Soininen and Teittinen 2019), and the application of broad morphological species concepts reinforced this idea (Vyverman et al 2010). Recent taxonomic studies, however, based on multiple lines of evidence (including genetic data), have revealed the existence of widespread (semi‐)cryptic diversity, restricted geographical distributions and regional endemism in many groups (April et al 2011, Kotov and Taylor 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, Soininen & Teittinen (2019) have recently summarized the main open questions concerning the spatial ecology of diatoms. This paper answers specifically their question 1 dealing with the key factors explaining diversity patterns in diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, at the subcontinental scale of our metacommunities, geographic barriers among the discrete hydrologic systems that comprised their habitats, may have contributed to dispersal limitation subsuming some of the climatic effect. Although environmental factors predict better the variance in diatom metacommunities compared to space (Soininen and Teittinen 2019), these factors are generally associated with nutrient level (Soininen 2007), which in our case was accounted for by nutrient context. Thus, nutrient contexts apparently determined the contribution of dispersal processes to community variation or influenced spatially‐structured climatic drivers.…”
Section: Discussionmentioning
confidence: 52%